Motivations for Refusal : Work, Value, and the Limits of Postworkerism - Gawne, Mark, (Social Sciences E-Books Online, Collection 2025., 2025)
In Motivations for Refusal: Work, Value, and the Limits of Postworkerism , Mark Gawne develops a critical account of how the affective politics of capital and class are formed and contested in contemporary arrangements of work, and offers a comprehensive critique of the postworkerist school of autonomist Marxism. Drawing on value critique and class composition analysis, the book challenges core assumptions of postworkerism and related theories of affective labour, while retaining their core insights. Moving beyond the limits of postworkerism, Gawne analyses how the integration of the affective sciences into management and workplace technologies constitutes a terrain of contestation in conditions of immaterial production. Motivations for Refusal explores how affective politics emerge in the contestation between labour and capital in their affective modes.